2018
DOI: 10.1590/s1980-220x2017041003410
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hemorrhagic complications with use of a radial compression device: a cohort study

Abstract: Objective: To examine the incidence of hemorrhagic complications in patients undergoing radial cardiac catheterization and using a hemostatic device for arterial compression. Method: A prospective cohort study conducted with patients undergoing elective cardiac catheterization in two hemodynamic laboratories in southern Brazil. The TR Band® radial compression device was used during 4 hours for hemostasis of the arterial puncture site. Hematomas and minor bleeding were the outcomes evaluated. Results: A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
1
4
0
7
Order By: Relevance
“…Regarding the safety of the radial artery hemostats device, this study found no statistically significant differences between the two groups in terms of the incidence of complications such as bleeding, ecchymosis, hematoma, skin damage, and local infection after removal of the device (P > 0.05), and this is also close to the findings reported in some other studies [11,[22][23][24].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the safety of the radial artery hemostats device, this study found no statistically significant differences between the two groups in terms of the incidence of complications such as bleeding, ecchymosis, hematoma, skin damage, and local infection after removal of the device (P > 0.05), and this is also close to the findings reported in some other studies [11,[22][23][24].…”
Section: Discussionsupporting
confidence: 89%
“…e application of radial hemostatic devices is widely used, especially in TR Band. Many studies have shown that TR Band has advantages in clinical use, such as simple operation, good hemostatic effect, and low complication rates [9][10][11]. In this study, a sample of a new radial artery hemostatic device based on a patent was evaluated by comparing its effectiveness, safety, and comfort with the TR Band and analyzing clinical data to provide new ideas and directions for the development of hemostats in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The TR band has been found in numerous studies to be more effective in achieving hemostasis. The incidence of hematoma or hemorrhage during TR band radial compression has been reported to be 14-26% in the literature [ 10 , 15 - 17 ]. In the study by Wang et al, 14% of the patients had a hematoma in the TR band group while 12% of the patients had a hematoma in the new compression device group.…”
Section: Discussionmentioning
confidence: 99%
“…9 Por isso, o encerramento vascular ao final do procedimento hemodinâmico, compreendido pela compressão manual e/ou por meio do uso de dispositivos de hemostasia, deve ser realizado com eficácia e efetividade. [6][7]10 Estudos…”
Section: Resumunclassified